Aromaterapi Integratif Menggunakan Uap Hangat dan Minyak Esensial untuk Mengurangi Nyeri Pasca Operasi Caesar - Dinda Ayu Setyo Putri; Lily Wahyuni Romadhon; Citra Setyo Dwi Andhini (CV. ALIM'SPUBLISHING, 2026)
Sectio Caesarea (SC) surgery causes severe acute pain due to abdominal and uterine wall trauma, which can delay mobilization and disrupt the lactation process. This study aimed to analyze nursing care and evaluate the effectiveness of simple inhalation therapy combining warm water and cajuput oil with lavender aroma in reducing pain intensity among post-SC patients. The research employed a descriptive qualitative case study design with a nursing care approach. The subjects consisted of 5 post-SC patients experiencing acute pain at Ruang Nifas. Data collection was conducted through interviews, direct observations using the Numeric Rating Scale (NRS) before and after the intervention, and nursing documentation over 3 days of care. The initial assessment revealed that all 5 respondents experienced moderate-to-severe acute pain, with pre-test scores ranging from 5 to 7. Following 10–15 minutes of daily inhalation therapy for 3 consecutive days, a consistent reduction in pain intensity was observed across all respondents, with post-test scores on the third day dropping to a range of 2 to 3 (mild pain). The patients also demonstrated more relaxed facial expressions and improved mobility comfort. In conclusion, the application of simple lavender inhalation therapy effectively reduces acute pain intensity in post-SC patients, making it a highly recommended independent nursing intervention in postpartum wards.